Water-silica force field for simulating nanodevices - Eduardo Cruz-Chú; Aleksei Aksimentiev; Klaus Schulten (J Phys Chem B, 2006)
Amorphous silica is an inorganic material that is central for many nanotechnology applications, such as nanoelectronics, microfluidics, and nanopore sensors. To use molecular dynamics (MD) simulations to study the behavior of biomolecules interacting with silica, we developed a force field for amorphous silica surfaces based on their macroscopic wetting properties that is compatible with the CHARMM force field and TIP3P water model. The contact angle of a water droplet on a silica surface served as a criterion to tune the intermolecular interactions. The resulting force field was used to study the permeation of water through silica nanopores, illustrating the influence of the surface topography and the intermolecular parameters on permeation kinetics. We find that minute modeling of the amorphous surface is critical for MD studies, since the particular arrangement of surface atoms controls sensitively electrostatic interactions between silica and water.
Keywords: Nanostructures; Silicon Dioxide; Water